Emerging benefits and drawbacks of α2‐adrenoceptor agonists in the management of sepsis and critical illness. (15th February 2021) - Lankadeva, Yugeesh R.; Shehabi, Yahya; Deane, Adam M.; Plummer, Mark P.; Bellomo, Rinaldo; May, Clive N.
Abstract : Agonists of α2 ‐adrenoceptors are increasingly being used for the provision of comfort, sedation and the management of delirium in critically ill patients, with and without sepsis. In this context, increased sympathetic and inflammatory activity are common pathophysiological features linked to multi‐organ dysfunction, particularly in patients with sepsis or those undergoing cardiac surgery requiring cardiopulmonary bypass. Experimental and clinical studies support the notion that the α2 ‐adrenoceptor agonists, dexmedetomidine and clonidine, mitigate sympathetic and inflammatory overactivity in sepsis and cardiac surgery requiring cardiopulmonary bypass. These effects can protect vital organs, including the cardiovascular system, kidneys, heart and brain. We review the pharmacodynamic mechanisms by which α2 ‐adrenoceptor agonists might mitigate multi‐organ dysfunction arising from pathophysiological conditions associated with excessive inflammatory and adrenergic stress in experimental studies. We also outline recent clinical trials that have examined the use of dexmedetomidine in critically ill patients with and without sepsis and in patients undergoing cardiac surgery.